Determination of Seleno-Amino Acids in Enriched-Selenium Tobacco by Reversed-Phase High-Performance Liquid Chromatography with Pre-column Derivatization - Pan1, Hongyang; Zeng2, Xiaoying; Zhu2, Baokun; He2, Liang; Liao2, Tougen; Zhe2, Wei; Wang1, Shuying; Jiang1, Bo; Wang2, Mingfeng (Asian Journal of Chemistry, 2013)
An analytical method has been developed for the simultaneous determination of selenocystine (SeCys), selenomethylcysteine (SeMeCys) and selenomethionine (SeMet). Three seleno-amino acids and 16 free amino acids were separated by high performance liquid chromatography on a reversed-phase column (Agilent Hypersil ODS column, 125 mm × 4.6 mm × 5 μm) with fluorometric detection (excitation wavelength at 340 nm and emission wavelength at 450 nm) by elution buffers based on sodium acetate with the flow rate 1 mL/min. The extraction methods of three seleno-amino acids and the chemical factors affecting the separation of the selenium species were optimized. All the three selenium compounds could be separated within 20 min. The method linearity, calculated for each seleno-amino acids, has a correlation coefficient higher than 0.990, in concentrations ranging from 0.1 to 10 mg/L (except for SeMeCys ranging from 0.1 to 100 mg/L). The stability of derivatives in acidified samples after ultrasonic was demonstrated. The limit of quantitation was estimated to be varying between 0.004 mg/L (SeMet) and 0.009 mg/L (SeCys) and recovery rates between 95.7 % (SeCys) and 112.9 % (SeMet). The repeatability of the method, expressed as R.S.D., ranged from 0.01 to 0.04 %. The presented method was applied for the quantitation of 16 amino acids and 3 seleno-amino acids contents in enriched-selenium Yunyan tobacco and ordinary Yunyan tobacco.